Chemical Composition and Biological Activities of Trans-Himalayan Alga Spirogyra porticalis (Muell.) Cleve - Kumar, Jatinder; Dhar, Priyanka; Tayade, Amol B.; Gupta, Damodar; Chaurasia, Om P.; Upreti, Dalip K.; Toppo, Kiran; Arora, Rajesh; Suseela, M. R.; Srivastava, Ravi B. (PLOS ONE, 2015)
The freshwater alga Spirogyra porticalis (Muell.) Cleve, a filamentous charophyte, collected from the Indian trans-Himalayan cold desert, was identified on the basis of morpho-anatomical characters. Extracts of this alga were made using solvents of varying polarity viz. n-hexane, acetonitrile, methanol and water. The antioxidant capacities and phenolic profile of the extracts were estimated. The methanol extract showing highest antioxidant capacity and rich phenolic attributes was further investigated and phytochemical profiling was conducted by gas chromatography-mass spectrometry (GC/MS) hyphenated technique. The cytotoxic activity of methanol extract was evaluated on human hepatocellular carcinoma HepG2 and colon carcinoma RKO cell lines. The anti-hypoxic effect of methanol extract of the alga was tested on in vivo animal system to confirm its potential to ameliorate oxidative stress. The antioxidant assays viz. ferric reducing antioxidant power (FRAP), 2,2'-azinobis-(3-ethylbenzothiazoline-6-sulfonic acid) diammonium salt (ABTS), 1,1-diphenyl-2-picrylhydrazyl (DPPH) and nitric oxide (NO) radical scavenging capacities, β-carotene-linoleic acid bleaching property and lipid peroxidation exhibited analogous results, wherein the algal extracts showed significantly high antioxidant potential. The extracts were also found to possess high content of total proanthocyanidin, flavonoid and polyphenol. GC/MS analysis revealed the presence of thirteen chemotypes in the methanol extract representing different phytochemical groups like fatty acid esters, sterols, unsaturated alcohols, alkynes etc. with substantial phyto-pharmaceutical importance. The methanol extract was observed to possess anticancer activity as revealed from studies on HepG2 and RKO cell lines. In the present study, S. porticalis methanol extract also provided protection from hypoxia-induced oxidative stress and accelerated the onset of adaptative changes in rats during exposure to hypobaric hypoxia. The bioactive phytochemicals present in this trans-Himalayan alga are of enormous interest and can be utilized sustainably for discovery of novel drugs against oxidative stress.